Design of the Tooth Profile of Pascal Curve Gear - Liu Yongping; Wang Peng; Xian Xilong; Zhang Shiyi (Jixie chuandong)
For the problem of generating Pascal curve gear tooth profile,the tooth profile of Pascal curve gear is designed via the conversion method of tooth profile and the non-cricular gear meshing principle,and its three dimensional modal is got by using Pro/E.The problem of dedendum transition curve generation is discussed and the transmission characteristic of a pair of Pascal curve gear are researched.It would be help to further study wire cutting of the Pascal gear on the basis of the involute profile which got by the conversion method of tooth profile.